Theological Hermeneutic Dialectics in the Interpretation of the Verses on the Nature of Allah: A Comparative Study of the Four Schools of Tafsir - Iffaty Zamimah; Hilyah Seffana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The divergence in the interpretation of Qur’anic verses concerning the divine attributes hasled to theological fragmentation, whichhas evolved into socio-cultural polarization, potentially undermining the harmony of contemporary Muslim communities. This study examines the hermeneutical dialectics of four theological schools in interpreting the verses on God’s attributes, focusing on their epistemological and practical implications within the Indonesian context. Employing a qualitative approach based on library research and al-Farmawi’s comparative analytical framework, this research analyzes three representative verses—Q.S. Tāhā[20]:5,Q.S. al-Fatḥ[48]:10,and Q.S. al-Raḥmān[55]:27—throughfour key exegeses: al-Mīzān (Shi‘a), al-Kashshāf (Mu‘tazilah), Mafātīḥ al-Ghayb (Ash‘ariyyah), and Taysīr al-Karīm (Salafi). The findings reveal distinct interpretive tendencies: the Shi‘a emphasize consistent philosophicalta’wīl;the Mu‘tazilah prioritizerational and philological reasoning;the Ash‘ariyyah construct a complex dialecticalhermeneutic;while the Salafi adopt a literalist approach with fluctuating methodological consistency. These divergences extend beyond theoretical discourse, manifesting in Indonesia’s socio-cultural contestations across digital spheres, religious institutions, and communal practices. This study argues that the diversity of interpretations regarding the divine attributes should not be perceived as a theological threat but rather as an epistemological richness that calls for a more inclusive and nuanced Qur’anic hermeneutic to preserve Muslim cohesion amid theological plurality. The novelty of this research lies in integrating theological and hermeneutical analysis within a comparative study of four major exegetical traditions and situating their interpretive dynamics within the contemporary socio-religious context of Indonesian Islam. This study contributes to advancing Qur’anic hermeneutics through a systematic analysis of methodological consistency across diverse theologicalschools.